2016
DOI: 10.1039/c6ce01642a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon-doped BiVO4@multi-walled carbon nanotubes with high visible-light absorption behavior, and evaluation of their photocatalytic properties

Abstract: In order to realize high efficiency visible-light absorption and electron-hole separation of bismuth vanadate (BVO), we synthesized carbon-doped BVO (C-BVO) with high visible-light absorption behavior. We used polyvinylpyrrolidone K-30 as a template and L-cysteine as the carbon source in a one-step hydrothermal synthesis method, and then obtained the carbon-doped BVO@multi-walled carbon nanotubes (C-BVO@MWCNT) by a two-step method. The carbon nanotubes were characterized by X-ray diffraction (XRD), Raman spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…The V 2 p core level spectrum in Figure 3d indicates that the binding energies (516.8 and 524.4 eV) for V 2 p are in accordance with former reports on V 5+ in BiVO 4 [34]. The XPS signals of O 1 s are 529.7 eV and 532.7 eV (Figure 3e) [14], respectively; this can be explained by the existence of O 2 − anions in BiVO 4 . According to Figure 3f, the peaks with binding energies of 159.3 eV and 164.6 eV are respectively related to Bi 4 f 7/2 and Bi 4 f 5/2 in BiVO 4 [35].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The V 2 p core level spectrum in Figure 3d indicates that the binding energies (516.8 and 524.4 eV) for V 2 p are in accordance with former reports on V 5+ in BiVO 4 [34]. The XPS signals of O 1 s are 529.7 eV and 532.7 eV (Figure 3e) [14], respectively; this can be explained by the existence of O 2 − anions in BiVO 4 . According to Figure 3f, the peaks with binding energies of 159.3 eV and 164.6 eV are respectively related to Bi 4 f 7/2 and Bi 4 f 5/2 in BiVO 4 [35].…”
Section: Resultssupporting
confidence: 86%
“…For instance, BiVO 4 has been doped with rare earth metals (e.g., Bi 4 V 2− x M x O 11− x (M = Gd, Nd, Gd, M = Nd) [10]), europium [11], transition metals (e.g., Ag-doped BiVO 4 [12] and Pd/BiVO 4 [13]), and C [14,15]. These doping systems can effectively reduce the band gap of BiVO 4 and increase its visible absorption range.…”
Section: Introductionmentioning
confidence: 99%
“…After further study, it was found that the generation of • OH was different from that of the study of Zhao et al . Figure shows the two radical signals under aerobic and anaerobic conditions.…”
Section: Resultsmentioning
confidence: 57%
“…The photocatalytic activity of a catalyst is determined by its capacity to absorb sunlight and separate excited electron–hole pairs . Many studies have reported the basic process of this photocatalytic reaction . To prove the formation process of radicals during the photocatalytic reaction in this study, ESR analysis was employed to detect • OH and • O 2 − radicals under NIR irradiation.…”
Section: Resultsmentioning
confidence: 98%
“…Carbonaceous materials such as CNTs, [269] and rGO [270] have been loaded to BiVO 4 with improved photocatalytic properties. Also, the decoration of conductive metal nanoparticles is a powerful path to induce surface plasmonic resonance (SPR) to photocatalytic systems with enhanced visible light absorption for improving the photocatalytic activity.…”
Section: Vanadium Oxide Heterostructures In Photocatalytic Hydrogen Ementioning
confidence: 99%